2020
DOI: 10.1107/s2052252520012725
|View full text |Cite
|
Sign up to set email alerts
|

Continuous flexibility analysis of SARS-CoV-2 spike prefusion structures

Abstract: Using a new consensus-based image-processing approach together with principal component analysis, the flexibility and conformational dynamics of the SARS-CoV-2 spike in the prefusion state have been analysed. These studies revealed concerted motions involving the receptor-binding domain (RBD), N-terminal domain, and subdomains 1 and 2 around the previously characterized 1-RBD-up state, which have been modeled as elastic deformations. It is shown that in this data set there are not well defined, stable spike co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 42 publications
2
36
0
Order By: Relevance
“…S5I), in line with our local resolution data (Fig. S5D) and a recent report (40). However, the motion directions of the associated ACE2-RBD in S-ACE2 complex are divergent to some extend from those of the up RBD in S-open, implying that ACE2 binding could alter the conformational dynamics of the up RBD and potentially the allosteric coordination of S1 subunits.…”
Section: Continuous Swing Motions Of Ace2-rbd In the Context Of Sars-supporting
confidence: 91%
“…S5I), in line with our local resolution data (Fig. S5D) and a recent report (40). However, the motion directions of the associated ACE2-RBD in S-ACE2 complex are divergent to some extend from those of the up RBD in S-open, implying that ACE2 binding could alter the conformational dynamics of the up RBD and potentially the allosteric coordination of S1 subunits.…”
Section: Continuous Swing Motions Of Ace2-rbd In the Context Of Sars-supporting
confidence: 91%
“…4, unclear if any additional conformational states other than those with either all three RBD domains in the closed state or only one RBD open state are biologically relevant. Specifically, Yurkovetskiy et al [44] observed an occupancy for states with two or three RBD domains in the open conformation, but these were not observed by Gobeil et al [30] and Xiong et al [34] or taken into consideration in several other structural studies [20][21][22][23][24]. As such, we employ the two-state model shown in Figure 2 [30] and Xiong et al [34].…”
Section: Conformational State Occupanciesmentioning
confidence: 97%
“…Several aspects of the dynamics of the Spike protein are being currently studied, with a range of particular goals: to evaluate the docking of small molecules to the RBD domain [19], to search for alternative target binding-sites for vaccine development [20], to understand residue-residue interactions and their effects on conformational plasticity [21] and to investigate the flexibility of different domains in particular conformational states [22].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in two of the three replicate simulations of cholesterol bound to the open spike, cholesterol in the site formed by the open subunit (site 3) migrates to an alternative site in the open structure. The proximity of this alternative site to the hinge region, which is important for conformational changes of the spike between the locked and open forms, [30, 36] suggests a possible mechanism by which cholesterol binding at this position may affect the dynamics and preferred conformation of the spike RBD, potentially stabilizing a form which presents the RBD for ACE2 binding.…”
Section: Discussionmentioning
confidence: 99%